Cold War Transgressions Christian Realism, Conservative Socialism, and the Longer 1960s - Edwards, Mark Thomas (2015)
This essay examines the convergence of the Protestant left and traditionalist right during the 1950s. Reinhold Niebuhr and the World Council of Churches challenged Cold War liberalism from within. As they did, they anticipated and even applauded the anti-liberalism of early Cold War conservatives. While exploring intellectual precursors of the New Left, this essay forefronts one forgotten byproduct of the political realignments following World War II: The transgressive politics of conservative socialism. Furthermore, this work contributes to growing awareness of ecumenical Christian impact within American life.
Keywords: Christian realism; Cold War; Conservativism; Ecumenism; Liberal Protestantism; Liberalism; New Left; Protestantism; Reinhold Niebuhr; World Council of Churches